Dogma, living and dead: selective engagement with the foundations of Christianity in Alexandre Kojève’s philosophy - Ivan Kurilovich (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
This article explores Alexandre Kojève’s philosophical interpretation of two fundamental tenets of Christian theology. Particular attention is given to his examination of the doctrines of the Incarnation and the immortality of the soul, as well as to his broader stance on theistic belief, understood as faith in an eternal Creator transcending the world. The study further situates Kojève’s reflections in dialogue with select thinkers of Russian religious idealism, notably Nikolai Berdyaev. Through a detailed analysis, the article elucidates the logical, anthropological, and epistemological foundations of Kojève’s engagement with Christianity, tracing their roots in Hegelian dialectics and Heideggerian phenomenology. This approach makes it possible to assess both the distinct and, at times, contradictory aspects of Kojève’s reflections on religion, highlighting their indispensability to his broader philosophical system. While acknowledging Christianity’s foundational role in the development of metaphysics and natural science, Kojève sought to demythologize its legacy, reinterpreting it as a source of epistemic inspiration and a reservoir of productive metaphors. Adopting a non-confessional perspective, the article examines the philosophy-theology dialogue, illustrating how rigorous philosophical analysis of dogmatic principles can enhance their understanding and reveal their enduring significance in contemporary cultural discourse. Moreover, the study extends and critically reassesses the internalist and inclusive strategy in the philosophy of science and culture, which aims to establish a shared space for dialogue irrespective of one’s adherence—or lack thereof—to any specific religious tradition.